2020
DOI: 10.1017/s0031182020000086
|View full text |Cite
|
Sign up to set email alerts
|

Detection methods and prevalence of transmission stages of Toxoplasma gondii, Giardia duodenalis and Cryptosporidium spp. in fresh vegetables: a review

Abstract: One of the ways of human parasitic infection is the accidental ingestion of vegetables contaminated with parasites, which represents a major human health hazard. This non-exhaustive review aims to evaluate studies carried out on five types of vegetables (lettuce, parsley, coriander, carrot and radish) since 2000, particularly the methods used for recovery, concentration, detection and identification of protozoan parasites such as Toxoplasma gondii, Giardia duodenalis and Cryptosporidium spp., and the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Another study in the Czech Republic reported a significantly higher contamination of T. gondii in vegetables collected from farm storage rooms than those from fields [64], indicating a higher chance of contamination of vegetables and fruits during processing and selling [78]. Therefore, the adaptation of good practices in every step between farm and fork, such as production, processing, storage and selling minimize the microbial contamination of vegetables and fruits.…”
Section: Risk Factors Involved In the Contamination Of Vegetables Andmentioning
confidence: 99%
“…Another study in the Czech Republic reported a significantly higher contamination of T. gondii in vegetables collected from farm storage rooms than those from fields [64], indicating a higher chance of contamination of vegetables and fruits during processing and selling [78]. Therefore, the adaptation of good practices in every step between farm and fork, such as production, processing, storage and selling minimize the microbial contamination of vegetables and fruits.…”
Section: Risk Factors Involved In the Contamination Of Vegetables Andmentioning
confidence: 99%
“…Giardia in environmental waters, seafood, and fresh produce Giardia causes water-and foodborne outbreaks of diarrheal illness globally [28]. In particular, waterborne transmission is of major importance in the epidemiology of the parasite and still constitutes a serious public health concern [8,22]. To date, Giardia is known to exist in eight distinct assemblages, or genotypes, from A to H, where A and B are infectious to humans.…”
Section: Ecology and Epidemiologymentioning
confidence: 99%
“…Surveillance studies from around the world reported widely varying contamination rates for the three protozoan in leafy greens, attributable to differing sampling strategies, geographic location, sanitation and detection methodologies. Parasitic (oo) cysts have usually been monitored in food matrices following three steps: elution, concentration and detection [22]. The difference in properties of the various food matrices could make it di cult to remove and detect protozoan (oo) cysts [2].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this standard is based on immunomagnetic separation technique followed by immuno uorescent assay for detection that are expensive, time consuming and require a microscopy expertise, making this method di cult to use for routine checks by food processors. Therefore, there have been a multitude of described methods worldwide for parasitic detection in vegetable matrices with different recovery e ciencies and detection levels [22]. This contributes to the under diagnosis of protozoan parasites in food.…”
Section: Discussionmentioning
confidence: 99%